Mobilização e transferência de agrotóxicos em uma lavoura de soja na bacia hidrográfica do arroio Guarda-Mor - Ragagnin, Melissa Rocha (2021)
The expansion of agricultural cultivation areas in Brazilian territory, coupled with the increase in the level of mechanization, the intensive use of fertilizers and pesticides and the adoption of inappropriate practices of use and management of the soil, can accelerate soil degradation process, water resources and the entire ecosystem. This process results in the mobilization and transfer of nutrients, sediments and pesticides to hydric bodies and deposition regions, caused by the increase in runoff and erosion rates. It is estimated that about 95% of the applied pesticides reach destinations other than their application site, with the largest receptor being the soil. Thus, evaluating the ways of mobilizing and transferring pesticides out of the application sites is necessary in order to understand the spatial dynamics and the entry of contaminants in hydric bodies. The present work proposes to study the transfer of pesticides from cultivated slopes, taking into account the connectivity between slopes, deposition zones and water bodies, in order to identify the psticides presence and transfer. The study was carried out on a slope located in the Arroio Guarda-Mor Basin, in the central region of the state of Rio Grande do Sul, Brazil, characterized by soybean cultivation. Soil samples were collected at depths 0 - 2.5 cm, 2.5 - 5 cm, 5 - 7.5 and 7.5 - 15 cm on the slope, in the upper segment and on deposition banks in order to verify the presence of pesticides in these matrices. Moreover, water samples were also collected during a rainfall event, in order to assess the hydric body. To assess the presence of pesticides in the receiving body, bottom sediments and water were collected from different points of the receiving body. Pesticides were detected in all water samples and all soil collection points in the present study, ranging between 0.01 and 0.52 mg / kg in the soil, 0.01 and 21.02 µg / L in the runoff, 1.32 and 0.02 µg / L in the weir water and between 0.01 and 0.018 mg / kg in the bottom sediments of the weir. The deposition zones proved to be of great importance in the pesticide transfer process, including the deposition zone between the slope and the water body that had the highest concentrations of pesticides in the study. Moreover, it can be verified that there is a transfer of pesticides through runoff, and the first rainfall event of the crop that generated runoff was the one of greatest magnitude in the pesticide transfer process.